Collaboration or Paradigm Shift?: Caveat Emptor and the Risk of Romance with Economic Models for Strategy and Policy Research - Hirsch, Paul M.; Friedman, Ray; Koza, Mitchell P. (Organization Science, 1990)
While the “formulation” or “strategy” side of business policy has always drawn appropriately from economic theory, we caution that, taken to its logical extreme, economic theory ignores the importance of implementation, implies lack of choice in organization decision-making, and makes the organization a nonentity. In this paper, we outline the fundamental differences between behavioral and economic approaches to business policy. These differences are highlighted by an illustration of their divergent perspectives on corporate “agency”.